2018
DOI: 10.1042/bcj20180424
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor potency varies widely among tumor-relevant human isocitrate dehydrogenase 1 mutants

Abstract: Mutations in isocitrate dehydrogenase 1 (IDH1) drive most low-grade gliomas and secondary glioblastomas and many chondrosarcomas and acute myeloid leukemia cases. Most tumor-relevant IDH1 mutations are deficient in the normal oxidization of isocitrate to α-ketoglutarate (αKG), but gain the neomorphic activity of reducing αKG to D-2-hydroxyglutarate (D2HG), which drives tumorigenesis. We found previously that IDH1 mutants exhibit one of two reactivities: deficient αKG and moderate D2HG production (including com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 53 publications
(95 reference statements)
0
39
0
Order By: Relevance
“…One of the most promising dual inhibitors is vorasidenib, and has been proposed for the treatment of GBM since it is able to cross the blood brain barrier [71]. Importantly, the response to IDH inhibitors is affected by the type of mutations [72]. Indeed, it has been demonstrated that R132Q mutation alters the catalytic site structure in such a way that the IDH1 inhibitors ML309, AGI-5198 and GSK864 are less potent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising dual inhibitors is vorasidenib, and has been proposed for the treatment of GBM since it is able to cross the blood brain barrier [71]. Importantly, the response to IDH inhibitors is affected by the type of mutations [72]. Indeed, it has been demonstrated that R132Q mutation alters the catalytic site structure in such a way that the IDH1 inhibitors ML309, AGI-5198 and GSK864 are less potent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that R132Q mutation alters the catalytic site structure in such a way that the IDH1 inhibitors ML309, AGI-5198 and GSK864 are less potent. By contrast they are instead more active against R132H-IDH1 or wild-type IDH1 expressing cells [72]. This aspect must be carefully considered in choosing the right inhibitor for the right mutant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…All proteins were expressed and purified using conditions published previously [ 3 , 33 ]. Purity (≥ 90%) was confirmed by SDS-PAGE, and IDH1 was flash frozen in liquid nitrogen and stored at 80 °C for no longer than 1.5 months.…”
Section: Methodsmentioning
confidence: 99%
“…Three phenotypes were characterized: The first phenotype involved depleted 2OG but moderate r -2HG and was associated with the most common R132H and R132C IDH1 mutations; the second exhibited moderate 2OG levels and high r -2HG levels and was associated with IDH1 R132Q ; the third phenotype was characterized by depleted 2OG but again high r -2HG levels, being associated with R132L ( 108 ).…”
Section: Metabolism Of 2hgmentioning
confidence: 99%
“…It seems that specific inhibitors should be designed for each mutation. For example, the mutant IDH1 R132Q was 10 5 -less sensitive to mutant inhibitors than IDH1 R132H ( 108 ). This was explained by the conformation of α-helices more closely resembling the wt enzyme.…”
Section: Metabolism Of 2hgmentioning
confidence: 99%